DEVELOPING SPEAKING MATERIAL THROUGH TASK BASED LANGUAGE LEARNING AT VOCATIONAL HIGH SCOOL IN LUBUKLINGGAU - Agus Triyogo; Ardayati Ardayati; Syaprizal Syaprizal (LP4MK STKIP PGRI Lubuklinggau, 2019)
The objectives of this study were (1) to design speaking materials using task based language teaching for SMK Negeri 3 Lubuklinggau and (2) to describe the strengths and the weaknesses of the speaking materials using Task Based Language teaching for SMK Negeri 3 Lubuklinggau. This research include to Educational Research and Development (R&D) using a simplified six steps of Borg and Gall’s model (1983). The result present that the product relies much on pertaining the KD of 2013 curriculum and the teacher expected that the students need to increase speaking skill since they have opportunity to speak English. The speaking materials were in line with students wants. The strengths of this product helped students to improve their speaking skill especially the vocabularies, the language function and the grammar used in spoken language. The tasks can attract the students to actively involve the teaching and learning process.